Biological evidence for a causal role of HPV16 in a small fraction of laryngeal squamous cell carcinoma - Halec, Gordana; Holzinger, Dana; Schmitt, Markus; Flechtenmacher, Christa; Dyckhoff, Gerhard; Höfler, Daniela; Bosch, Franz X.; Pawlita, Michael (British journal of cancer, 2013)
Human papillomavirus (HPV) is a causal factor in virtually all cervical and a subset of oropharyngeal squamous cell carcinoma (OP-SCC), whereas its role in laryngeal squamous cell carcinoma (L-SCC) is unclear.
Gesehen am 25.02.2021